Sunday

April 20, 2014

April 20, 2014

Posted by **Anonymous** on Friday, March 22, 2013 at 4:39pm.

- algebra -
**Reiny**, Friday, March 22, 2013 at 5:06pmafter a few tries I found f(4) = 0

so (x-4) is a factor

by synthetic long division I got

(x-4)(4x^2 + 35x - 9)

= (x-4)(x+9)(4x - 1)

What does the fact that

f(x) = -9 have to do with it.?

Did you mean to say: f(9) = 0 , that would have given me the clue that x+9 is a factor.

**Related Questions**

math,algebra - Can someone explain this to me plese: to factor a number you.... ...

Math - Can you factor these for me? 12x^3 + 6x^2 - 3x - 2 2x^2 +x - 6 25 - 4(x^2...

algebra2 - Solve each of the following quadratic equations. can some explain how...

algebra - factor: 9w - w^3 = 3w(3-w^2) m^4 - n^4 = (m-n)^2(m-n)^2 are these ...

maths - how do i change x^2-4x-32=0 into (x+4)(x-8)=0 x^2-4x-32=0 => x^2-8x+...

Math.... again......!!!!!!... - A fraction is equivelant to 4/5. The sum of the ...

algebra - did I do this right and if not can you please help me. Solve. 4(x + 7...

Algebra - use factor theorem to determine whether x+2 is a factor of f(x). if it...

Algebra - x^2+2x-15/4x^2/x^2-25/2x-10 You need to use parentheses to clarify the...

algebra - factor the expression 4x^2+25x+36